Challenges to upward mobility: perceptions of black women in the South African financial industry - Ngwenya, Nasia Nelisiwe (My University, 2016)
The 21st century workplace is characterised by gender and racial diversity and intergroup contact which the world has never experienced before. This has far reaching implications for organisations given that a link has been made between an organisation’s improved financial performance and the presence of women and minorities in senior and executive roles. Despite increasing racial and gender diversity in the South African workplace, positions within management do not accurately represent this occurrence. Statistics show that White males still account for more than a two thirds majority in terms of representation at senior and top management levels, and Black women have the lowest representation. This research therefore explored the perceptions that Black women had regarding the barriers to their upward mobility in the South African Financial industry. The focus was on twenty Black women in varying occupational levels of middle, senior and top management. A combination of topics related to glass ceiling theory was used to derive statements which were presented to participants, using Q methodology, the study sought to discover and explore the patterns of perceptions in relation to these themes. Meta-stereotypes were also introduced as another theme to explore whether they existed to serve as a psychological barrier which influenced the perceptions and subsequent workplace attitudes and behaviours of the participants. The findings revealed two patterns of perceptions. The first was inward looking and pertained to the participants’ perceptions regarding their competence, hard work and career-mindedness. The second was more outward looking and pertained to the ambition of participants despite the challenges they perceived to exist. Negative meta-stereotypes were not found, indicating the absence of a negative psychological barrier to influence the perceptions of the participants.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Arts in Organisational Psychology November 2016
Keywords: Leadership in women--South Africa; Women excecutives